Effect of nanoclay on durability and mechanical properties of flax fabric reinforced geopolymer composites - Assaedi, Hasan; Shaikh, Faiz; Low, It Meng (Elsevier, 2017)
The main concern of using natural fibres as reinforcement in geopolymer composites is the durability of the fibres. Geopolymers are alkaline in nature because of the alkaline solution that is required for activating the geopolymer reaction. The alkalinity of the matrix, however, is the key reason of the degradation of natural fibres. The purpose of this study is to determine the effect of nanoclay (NC) loading on the mechanical properties and durability of flax fabric (FF) reinforced geopolymer composites. The durability of composites after 4 and 32 weeks at ambient temperature is presented. The microstructure of geopolymer matrices was investigated using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The results showed that the incorporation of NC has a positive impact on the physical properties, mechanical performance, and durability of FF reinforced geopolymer composites. The presence of NC has a positive impact through accelerating the geopolymerization, reducing the alkalinity of the system and increasing the geopolymer gel. © 2017 The Ceramic Society of Japan and the Korean Ceramic Society .